Effects of COVID-19 on Papua New Guinea’s food economy: A multi-market simulation analysis - Diao, Xinshen; Dorosh, Paul A.; Fang, Peixun; Schmidt, Emily (International Food Policy Research Institute, 2020)
Developments in the agricultural economy of Papua New Guinea have major impacts on household food consumption decisions. A household’s ability to produce and sell food is affected by climate and associated agricultural potential, market opportunities (domestic, import and export) and unexpected shocks. Each of these factors affects the overall food system, thereby influencing production and consumption of all food products and the markets in which they are traded. The COVID-19 pandemic has presented a challenge far more complex than an agricultural production shock, such as those due to El Niño or pests. Rather than directly affecting agricultural output and rural household welfare, the COVID-19 pandemic has affected economies across the globe via trade disruptions (logistic challenges; international trade barriers), social distancing policies (domestic food market and nonessential business closures), and transportation restrictions (road closures; air travel cancellations). The measures aimed to curb the spread of COVID-19 have affected household incomes via urban job losses, reduced market interaction, and dramatic changes in world food prices. While rice prices have increased, luxury food prices, such as for chocolate (i.e. cocoa), have decreased. PNG’s unique and highly varied biophysical landscape has shaped agricultural production patterns, outcomes, and livelihoods for centuries. Understanding how the PNG agrifood economy and resulting household consumption is affected by COVID-19 therefore requires attention to linkages and substitution effects across various products and the markets in which they are traded.